THE EFFECT OF E-LEARNING-BASED PROJECT LEARNING ON STUDENTS MOTIVATION - Astari, Annisa Dwi; Utami, Citra; Pratiwi, Desty Kurnia; Subroto, Prawidi Wisnu (STIE Kusuma Negara, 2020)
The purpose of this study was to determine whether there were differences in learning motivation between students given project-based and conventional learning. This quantitative research method was conducted in class VIII YPI Al-Maghfiroh Gandasari Tangerang, Tangerang City in Mathematics with a sample of 24 people. The independent variable in this study is student motivation with 8 indicators, namely: a) Persevering in the task; b) Resilient in facing difficulties; c) Showing interest in various problems; d) Prefer to work independently; e) Get bored with routine tasks quickly; f) Can defend his opinion; g) It is not easy to give up what is believed; h) Happy to find and solve complex problems. Then arranged in the form of a questionnaire instrument with a total of 15 items. The instrument has been tested for validity by expert validators. While the dependent variable is the Mathematical formative test scores derived from documentation data on average student achievement in learning. Based on the Hypothesis test obtained, the magnitude of the correlation coefficient (r) that is equal to 0.5482 is greater than 0.491 with a significant level of 5%. Thus it can be concluded that Ha is accepted, that is